A BRIEF REVIEW ON MEDICATED CHEWING GUM’S - Jain, Saloni; Khinchi, M. P.; Singh, S. P.; Nama, Nitin; Gauttam, Narendra (Asian Journal of Pharmaceutical Research and Development, 2017)
The present invention is directed to chewing-gum preparations which are particularly useful for treating gastroesophageal reflux disease. Typically, the chewing-gum preparation comprises a chewing-gum base and more than one ingredient selected from the group consisting of an acid neutralizing agent, an anti-gas agent, and an acid production inhibitor, and desirably all three ingredients.